Developing a SWOT roadmapping technique for managing strategy, operations, and technology interfaces - Yee, Choy Leong; Teoh, Kenny Guan Cheng; Liaw, Winnie Wei Yu (Institute for Manufacturing, University of Cambridge, 2011)
This paper reports a research on developing a SWOT roadmapping technique for managing strategy, operations, and technology of a firm. The technique has incorporated the concepts of technology roadmapping, strategic charting, and SWOT to help managers in developing strategic plans and capabilities that support business requirement. In order to operationalise the technique, it was tested in two laboratory experiments and four companies. The results show mixed opinions of positive and negative feedbacks from the respondents. The findings of this research are of interest of many academics and managers. The implications of the findings to both theory and practice are discussed.